Prognostic factors related to ambulation deterioration after 1-year of geriatric hip fracture in a Chinese population - Ronald Man Yeung Wong; Jianghui Qin; Wai Wang Chau; Ning Tang; Chi Yin Tso; Hiu Wun Wong; Simon Kwoon-Ho Chow; Kwok-Sui Leung; Wing-Hoi Cheung (Scientific Reports, 2021)
Abstract The objective of this study was to investigate the prognostic factors predicting the ambulation recovery of fragility hip fracture patients. 2286 fragility hip fracture patients were collected from the Fragility Fracture Registry in Hong Kong. Predictive factors of ambulation deterioration including age, gender, pre-operation American Society of Anesthesiologists grade, pre-fracture mobility, delay to surgery, length of stay, fracture type, type of surgery, discharge destination and complications were identified. Patients with outdoor unassisted and outdoor with aids ambulatory function before fracture had 3- and 1.5-times increased risk of mobility deterioration, respectively (Odds Ratio (OR) = 2.556 and 1.480, 95% Confidence Interval (CI) 2.101–3.111 and 1.246–1.757, both p < 0.001). Patients living in old age homes had almost 1.4 times increased risk of deterioration when compared to those that lived in their homes (OR = 1.363, 95% CI 1.147–1.619, p < 0.001). The risk also increased for every 10 years of age (OR = 1.831, 95% CI 1.607–2.086, p < 0.001). Patients in the higher risk ASA group shows a decreased risk of ambulation deterioration compared to those in lower risk ASA group (OR = 0.831, 95% CI 0.698–0.988, p = 0.038). Patients who suffered from complications after surgery did not increased risk of mobility decline at 1-year post-surgery. Delayed surgery over 48 h, delayed discharge (> 14 days), early discharge (less than 6 days), and length of stay also did not increased risk of mobility decline. Male patients performed worse in terms of their mobility function after surgery compared to female patients (OR = 1.195, 95% CI 1.070–1.335, p = 0.002). This study identified that better premorbid good function, discharge to old age homes especially newly institutionalized patients, increased age, lower ASA score, and male patients, correlate with mobility deterioration at 1-year post-surgery. With the aging population and development of FLS, prompt identification of at-risk patients should be performed for prevention of deterioration.